TRANSFORMASI DIGITAL DESA SIMONGAGROK DALAM MENINGKATKAN EFEKTIVITAS IMPLEMENTASI E-GOVERNMENT DI ERA SOCIETY 5.0 - santosa santosa (MAJAPAHIT POLICY, 2025)
As the smallest government unit, villages play a crucial role in managing data and information related to the population and village development activities. However, Simongagrok Village still uses manual methods for data management and information dissemination to the community. This creates various obstacles, such as slow access to information, lack of transparency, and difficulties in monitoring development programs. To address these issues, the planning and creation of a Village Information System (SID) website with a village profile is an effective solution. The purpose of this community service is to design and develop a SID website for the village to document activities, present village profile information, process population data, document activities, and digitally disseminate public information. Quantitative methods are used. The result of this community service is a SID website with key features such as demographic data management, public service information, village news, and development activity documentation. This website is expected to improve the quality of village government services, facilitate public access to information, and encourage transparency and public participation in village development.